Interstitial macrophage phenotypes in Schistosoma-induced pulmonary hypertension - Kumar, Rahul; Kumar, Sushil; Mickael, Claudia; Fonseca Balladares, Dara; Nolan, Kevin; Lee, Michael H.; Sanders, Linda; Nilsson, Julia; Molofsky, Ari B.; Tuder, Rubin M.; Stenmark, Kurt R.; Graham, Brian B. (Frontiers in Immunology, 2024)
Background: Schistosomiasis is a common cause of pulmonary hypertension (PH) worldwide. Type 2 inflammation contributes to the development of Schistosoma-induced PH. Specifically, interstitial macrophages (IMs) derived from monocytes play a pivotal role by producing thrombospondin-1 (TSP-1), which in turn activates TGF-β, thereby driving the pathology of PH. Resident and recruited IM subpopulations have recently been identified. We hypothesized that in Schistosoma-PH, one IM subpopulation expresses monocyte recruitment factors, whereas recruited monocytes become a separate IM subpopulation that expresses TSP-1. Methods: Mice were intraperitoneally sensitized and then intravenously challenged with S. mansoni eggs. Flow cytometry on lungs and blood was performed on wildtype and reporter mice to identify IM subpopulations and protein expression. Single-cell RNA sequencing (scRNAseq) was performed on flow-sorted IMs from unexposed and at day 1, 3 and 7 following Schistosoma exposure to complement flow cytometry based IM characterization and identify gene expression. Results: Flow cytometry and scRNAseq both identified 3 IM subpopulations, characterized by CCR2, MHCII, and FOLR2 expression. Following Schistosoma exposure, the CCR2 + IM subpopulation expanded, suggestive of circulating monocyte recruitment. Schistosoma exposure caused increased monocyte-recruitment ligand CCL2 expression in the resident FOLR2 + IM subpopulation. In contrast, the vascular pathology-driving protein TSP-1 was greatest in the CCR2 + IM subpopulation. Conclusions: Schistosoma-induced PH involves crosstalk between IM subpopulations, with increased expression of monocyte recruitment ligands by resident FOLR2 + IMs, and the recruitment of CCR2 + IMs which express TSP-1 that activates TGF-β and causes PH.